Hubungan Dukungan Petugas Kesehatan, Dukungan Keluarga dan Pengetahuan Ibu dengan Pemberian ASI Eksklusif - fitri utari; Siti Aisyah; Rizki Amalia (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The Government's efforts to support the increase in exclusive breastfeeding have resulted in agreements or various recognitions, both globally and nationally, which aim to protect, promote, and support breastfeeding. It is hoped that every baby has the right to get exclusive breastfeeding and every mother can give breast milk. This study aims to determine the relationship between health worker support, family support and knowledge with exclusive breastfeeding for infants aged 7-12 months in the Tanjung Baru Health Center Work Area, Ogan Komering Ulu Regency in 2021. The design of this study was an analytical survey using a cross sectional research design. . The population in this study were all mothers who had babies aged 7-12 months in January-July 2021, which were 38 respondents and the number of samples was 38 respondents. The sampling technique used is accidental sampling. Data analysis used chi square statistical test with = 0.05. The results of this study found that there was a relationship between family support (p value = 0.02), support from health workers (p value = 0.01) and knowledge (p value = 0.003) with exclusive breastfeeding. The results of the research can be used as a reference to improve counseling and socialize the exclusive breastfeeding program to the community.